ANALISIS STABILITAS PROSES WWTP BERDASARKAN COD MENGGUNAKAN STATISTICAL QUALITY CONTROL DI PT. A - Verra Syahmer; Maryam; Wahyu Yasril; Hermiza Mardesci (JURNAL TEKNOLOGI PERTANIAN, 2026)
This study aims to analyze the quality control of Chemical Oxygen Demand (COD) levels in the Waste Water Treatment Plant (WWTP) process at PT. A using the Statistical Quality Control (SQC) method. The data used consist of primary data obtained from laboratory testing and secondary data from company records. The analysis was conducted using X̄ and R control charts to monitor process stability and fishbone diagrams to identify the root causes of deviations. The results indicate that the COD treatment process still shows variations, suggesting that the process is not fully under statistical control during certain periods. The main contributing factors include human, method, machine, material, and environmental aspects. Therefore, continuous improvement efforts are required to ensure that the wastewater quality meets the established standards.